TRADITIONAL SILAT COLLEGE ALUMNI COMMUNICATION LANGGA IN BULONTALA VILLAGE SUWAWA GORONTALO (British Journal of Global Ecology and Sustainable Development, 2024)
Study this aim for know about: (1) for know pattern communication among college alumni martial arts traditional langga in the village Bulontala Subdistrict Suwawa, Gorontalo, (2) for identify obstacles communication among college alumni martial arts traditional langga in the village Bulontala Subdistrict Suwawa, Gorontalo. Types of research This is descriptive qualitative, the effortful describe something symptom social. In other words , research This aim For describe characteristic something in the middle taking place at the moment study . Study This use technique data collection with interview in-depth , observation and study References . Research result This describe pattern established communication among college alumni martial arts traditional langga very harmonious . Alumni from various level and year train recorded complete in the current college alumni book stored neat At home the residence of the great teacher Langga “Bapu Tani” in the village Bulontala Subdistrict Suwawa Gorontalo. Alumni have group whatsapp For intertwine communication and information as well as several alumni who had the opportunity present every Evening Friday For visit supreme teacher and see the students who are train. Obstacle communication from college alumni martial arts traditional langga is place stay with each other far apart make alumni difficult meet with large amount.